Open Access movement in Latvia - Gudakovska, Iveta; Rozenberga, Gita; Lapsa, Evija (My University, 2014)
This article gives information about the situation of Open Access development in Latvia between 2009 and 2013. The Library of the University of Latvia has made a serious effort to inform the scientific community through different activities and preparation of information materials. The University of Latvia Library created the institutional e-resource repository of the University of Latvia that can be served as a pilot project for further development of the repositories in Latvia.
Keywords: Open Access; Open Access movement; Open Access initiative; Open Access project